O papel das políticas públicas no desenvolvimento de sistemas agroflorestais no Brasil - Ballerini, Ariel Pollo (2023)
Climate change is a reality and its effects directly affect society, including the production of food and commodities. Given this scenario, the need to face the consequences of climate change leads to studies to verify alternatives for agricultural production that are sustainable and compatible with contemporary reality. Agroforestry systems (AFS) have socioeconomic and environmental benefits, and are the subject of international studies that evaluate the factors that determine their success. In order to be successful in the implementation of SAFs, and maximum use of their advantages, it is necessary that the State acts in the regulation of markets, in the incentives to the use of the technique through credit lines and payment for environmental services, among other aspects that are up to it. In this sense, the objective of this work is to identify the role that public policies play in the development of SAFs in Brazil, highlighting the programs and laws that contemplate national agriculture and that have an impact on the expansion of the use of agroforestry. Brazil has a legal framework that puts sustainability in agriculture on the agenda, as well as programs that propose investments in agroforestry, but there is no direct and specific direction of public effort for the development of SAFs in the country.